THE POTENTIAL DANGER TO ASCVD RISK REDUCTION: A RARE CASE OF INCLISIRAN INDUCED VASCULITIS - Sumair Ozair, DO (Elsevier, 2024)
Therapeutic Area: Pharmacologic Therapy Case Presentation: A 62-year-old male with coronary artery disease, hypertension, hyperlipidemia, and osteoarthritis complained of arthralgias, pharyngeal ulcers, ear fullness, and subjective fever. Symptoms began after receiving his inclisiran injection. Physical exam demonstrated petechial rash on extremities, injected conjunctivae, and trace edema in extremities. Laboratory workup showed elevated leukocytes, ESR and CRP with negative infectious workup. Urinalysis demonstrated hematuria and proteinuria with normal kidney function. The pharyngeal ulcers were evaluated by CT of the neck which incidentally demonstrated multiple pulmonary lesions concerning for metastatic disease. Pulmonology was consulted and biopsy of these lesions were obtained showing acute fibrinous and organizing pneumonia with granulomatous components. Consequentially, bronchial alveolar lavage was performed which was suspicious for a vasculitic process. Autoimmune workup revealed an elevated c-ANCA, proteinase 3 antibody, and rheumatoid factor. Given these findings, he was diagnosed with granulomatosis with polyangiitis and treated with steroids. Patient showed linear improvement and was discharged home with outpatient rheumatology referral. Background: Statin therapy is indicated in patients with moderate to high Atherosclerotic Cardiovascular Disease risk scores. Adjunct therapy may be considered in patients with persistent hyperlipidemia despite statin therapy. Proprotein convertase substilisin/kexin type 9 (PCSK9) is an enzyme encoded by the PCSK9 gene that binds to LDL receptors on hepatocytes which leads to higher levels of LDL-C. Inclisiran is a PCSK9-inhibitor that blocks the synthesis of that enzyme. The most common adverse effects of inclisiran include arthralgias and myalgias. Conclusions: Although data is limited linking inclisiran with vasculitis, this patient's history is suggestive of an association. Biological molecules have been described to cause vasculitides. Complications from these medications can occur at any point after administration. The mechanism of these vasculitides is poorly understood but it is speculated they can trigger an increased pro-inflammatory response. Rheumatologic reactions secondary to biological therapy typically exhibit complete resolution of symptoms after drug cessation. However, in some cases, corticosteroid therapy and immunosuppressive agents may be necessary for treatment. The adverse effects of inclisiran still need to be further studied. Despite vasculitides being a rare side effect of biological molecules, it is critical to keep this in mind as a possible reaction when prescribing PCSK9-inhibitors.